Organizational change as the key for a successful implementation of digital transformation : the case of ING - Außenhofer, Mariska (2020)
In our rapidly changing world, it becomes imperative for companies to adapt to current condi-tions to stay both competitive and profitable. For them, it is essential not only to introduce new technologies to embrace continuous learning and adaptability, but also to change the or-ganizational structure accordingly and train new ways of working. To demonstrate a real-life example, I developed a teaching case about the organizational transformation of the ING bank. The case intends to demonstrate an exemplary organizational change of a global bank in response to a rapidly changing business environment, coming along with digital transformation. ING’s management board, together with agile coaches, fundamentally reorganized the organization and introduced new ways of working and being agile, to move forward faster and successfully in a deeply disruptive world. The case clearly illustrates the importance of people and culture, together with a corporate growth mindset, in the organization, to sustain a competitive advantage in a changing business environment. Although ING was not undergoing a crisis, it did not keep the organizational change from happening. The Bank’s intention was to look beyond, in order to better face challenges con-cerned with environmental changes, and to boost performance as well as employee and cus-tomer satisfaction.